Evaluation of Fear and Peritraumatic Distress during Covid-19 pandemic in Brazil - Abad, Alberto (2020)
Covid-19 pandemic continues to spread exponentially worldwide, especially in America. By mid-June, 2020, Brazil is one of the most aﬀected countries with more than one million cases and up to 50,000 deaths. This study aims to assess the fear and peri-traumatic stress during the Covid-19 pandemics in Brazil, to enhance infection control methods, appropriate interventions, and public health policies. A cross-sectional survey has been conducted from April 12th to 18th using the Peri-Traumatic Distress Scale (CPDI) and the Fear Scale (FCV-19S) aiming to measure the peri-traumatic stress and fear as psychological reactions during the Covid-19 pandemic. For that purpose, an online spreadsheet was used to send the questionnaire and scales to a sample of 1844 participants as a collecting information tool. Both scales showed a correlation factor of (r=0,660). Results highlight significant gender differences as in both scales women’s mean scores are higher showing that it is paramount that women’s voices were represented in policy spaces as socially constructed gender roles place them in a strategic position to enhance multi-level interventions (primary and secondary effects of Covid-19), equitable policies, and new approaches to control the pandemic.